CO Responses of Sensors Based on Cerium Oxide Thick Films Prepared from Clustered Spherical Nanoparticles - Izu, Noriya (Molecular Diversity Preservation International (MDPI), 2013)
Various types of CO sensors based on cerium oxide (ceria) have been reported recently. It has also been reported that the response speed of CO sensors fabricated from porous ceria thick films comprising nanoparticles is extremely high. However, the response value of such sensors is not suitably high. In this study, we investigated methods of improving the response values of CO sensors based on ceria and prepared gas sensors from core-shell ceria polymer hybrid nanoparticles. These hybrid nanoparticles have been reported to have a unique structure: The core consists of a cluster of ceria crystallites several nanometers in size. We compared the characteristics of the sensors based on thick films prepared from core-shell nanoparticles with those of sensors based on thick films prepared from conventionally used precipitated nanoparticles. The sensors prepared from the core-shell nanoparticles exhibited a resistance that was ten times greater than that of the sensors prepared from the precipitated nanoparticles. The response values of the gas sensors based on the core-shell nanoparticles also was higher than that of the sensors based on the precipitated nanoparticles. Finally, improvements in sensor response were also noticed after the addition of Au nanoparticles to the thick films used to fabricate the two types of sensors.